The Role Of The Service Sector In The Formation Of Post-Industrial Society - Urunbaeva Yulduz Pirnazarovna; Umidov Davlatbek Umid o‘g‘li, Tinchlikova Nilufar Sirojiddin qizi, Norxo’jayev Kozimjon Fozil o‘g‘li (Research Parks Publishers, 2023)
In this article, the role of the service sector in the formation of the post-industrial society has been demonstrated.